2013
DOI: 10.1080/10408398.2011.574804
|View full text |Cite
|
Sign up to set email alerts
|

Application and Opportunities of Pulses in Food System: A Review

Abstract: Pulses are highly nutritious seeds of pod-bearing leguminous plants, specifically dry peas, lentils, and chickpeas. US farmers harvest about 2.6 million pounds of pulses every year but 75% of this is being exported internationally because of its increased consumption in the developing countries. In the current scenario, increasing costs of production, bad economy, and fluctuating food commodity prices have made a strong case for US producers to seek opportunities to increase domestic consumption of pulses thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(144 citation statements)
references
References 77 publications
7
133
0
4
Order By: Relevance
“…This applies to many communities in developing countries who cannot easily afford animal sources of dietary protein. The relatively high carbohydrates content and energy values of the lablab seeds observed in this study are similar to those observed in other studies (Asif et al, 2013;Nakitto et al, 2015;Nazni & Devi, 2016). They are also within the range of the other most commonly consumed legume grains (Sánchez-Chino et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…This applies to many communities in developing countries who cannot easily afford animal sources of dietary protein. The relatively high carbohydrates content and energy values of the lablab seeds observed in this study are similar to those observed in other studies (Asif et al, 2013;Nakitto et al, 2015;Nazni & Devi, 2016). They are also within the range of the other most commonly consumed legume grains (Sánchez-Chino et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Se aconseja que los carbohidratos ingeridos sean complejos, porque ayudan a mantener de forma más constante los niveles de glucosa sanguínea (9).…”
Section: Introductionunclassified
“…Because of their nutrient profile (high protein, oil and fiber content), seeds of grain legumes present tremendous opportunity to be used in a variety of processed human food products or as livestock or aquaculture feed [7,90]. If the domesticate has a similar nutritional profile and the functional attributes of an existing annual grain legume, immediate market opportunities could be available for its commercialization as a substitute without an extensive marketing strategy.…”
Section: High Value Productsmentioning
confidence: 99%
“…A major global source of plant-based proteins, they provide ten percent of the dietary requirements of proteins worldwide [90]. As such, grain legumes are significant components in the diets of people living within subsistence farming communities, in parts of the world where animal proteins are scarce or expensive and of those who choose to be vegetarians [91].…”
Section: Nutritional Profilementioning
confidence: 99%